Parenting Patterns for Students in Improving the Quality of Muraja'ah in the Era of Digital Distraction - Ahmad Ardhi Mauluddin Sitorus (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the parenting patterns of students in improving the quality of Quranic recitation in the era of digital distractions at the Darul Qur'an Islamic Boarding School in Deli Serdang. The development of digital technology, characterized by the high use of gadgets and social media among teenagers, presents challenges to the consistency, focus, and discipline of students in maintaining Quranic recitation memorization. This condition demands an adaptive and effective parenting pattern to maintain the quality of recitation. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, with research subjects including Islamic boarding school caretakers, tahfidz ustadz, and students. Data analysis was carried out through data reduction, data presentation, and conclusion, and its validity was tested through triangulation of sources and techniques. The results of the study indicate that the parenting pattern applied is a combination of authoritarian and democratic (authoritative) patterns that emphasize discipline, supervision, two-way communication, and the proportional application of rewards and punishments. Recitation activities are carried out in a structured manner through daily schedules, memorization submissions, and periodic evaluations. Factors influencing the quality of muraja'ah include students' internal motivation, the Islamic boarding school environment, and regulations on device use. This research contributes to an adaptive parenting model for maintaining the quality of muraja'ah amidst the challenges of the digital era